Hukum Perkawinan Adat Samawa: Menyelaraskan Kearifan Lokal dengan Hukum Nasional - Putra, Rifky Anantha; Rahayu, Mella Ismelina Farma (Al-Ishlah: Jurnal Ilmiah Hukum, 2023)
This research aims to analyze and understand how integrating the Samawa tribe’s local wisdom in the practice of indigenous marriage can occur harmoniously and in alignment with Indonesia’s national law. This research uses an inductive qualitative analysis. Inductive analysis is an approach that begins with field facts, analyzes them based on relevant legal theories and arguments, and ultimately yields a conclusion. The results show that Samawa indigenous marriage law can integrate harmoniously with national law. This integration encompasses indigenous law, where the Tana Samawa Indigenous Institution is crucial in preserving local wisdom. The existence of this indigenous institution, regulated by Sumbawa Regency Regulation Number 10 of 2015, demonstrates the Regency Government’s commitment to integrating local wisdom with the national legal system. In indigenous marriage, this integration ensures that local wisdom remains valid under indigenous law and has legality under Law Number 1 of 1974. Challenges and obstacles in preserving Samawa indigenous marriage, require a comprehensive approach that includes education, documentation of customs, and promotion of local wisdom through modern technology. Therefore, it is recommended that the Tana Samawa Indigenous Institution continue to strengthen the preservation and development of local wisdom through comprehensive education programs and documentation, and forge more intensive cooperation with the Regency Government and educational institutions. The Department of Education and Culture of Sumbawa Regency is recommended to integrate local wisdom material into the formal and non-formal education curriculum, and support cultural preservation initiatives by providing adequate facilities and resources. Samawa indigenous people are recommended to actively participate in the preservation of customs, support programs run by the indigenous institution and government, and use modern technology to document and promote their traditions, ensuring that local wisdom values remain alive and respected in everyday life.